Organinteraktion Leber und Niere - Roedl, Kevin; Jarczak, Dominik; Fuhrmann, Valentin (DMW - Deutsche Medizinische Wochenschrift, 2017)
Alterations of the kidney function can be observed often in patients with liver diseases. Different mechanisms are leading to alterations in kidney funciton in these patients. New onset of kidney function alterations in patients with acute- or chronic liver disease often leads to acute kidney injury. This Review will inform you about the most importatant clinical interactions of the kidneys and the liver.
Keywords: Organinteraktionen; Leberzirrhose; akutes Nierenversagen; Hepatorenales Syndrom